Communication research conditions in Brazil - Neto, Antônio Fausto (2008)
The research activity in general, and specifically in this area, is a set of initiatives of a public nature that, over the years, has been characterized as support to institutions and researchers. This support is materialized through agencies and public resources destined to agents and public bodies that are responsible for research policies and initiatives in Brazil.